A novel electrochemical nicotine sensor based on cerium nanoparticles with anionic surfactant. Issue 64 (12th July 2015) - Fekry, A. M.; Azab, S. M.; Shehata, M.; Ameer, M. A.
<x xml:space="preserve">Abstract</x> A novel promising electrochemical nicotine (NIC) sensor was prepared by electrodeposition of Ce-Nanoparticles on a carbon paste electrode (CPE).